2019
DOI: 10.1161/strokeaha.119.024889
|View full text |Cite
|
Sign up to set email alerts
|

Thrombectomy Outcomes of Intracranial Atherosclerosis-Related Occlusions

Abstract: Background and Purpose— Intracranial atherosclerosis (ICAS) is an important cause of large vessel occlusion and poses unique challenges for emergent endovascular thrombectomy. The risk factor profile and therapeutic outcomes of patients with ICAS-related occlusions (ICAS-O) are unclear. We performed a systematic review and meta-analysis of studies reporting the clinical features and thrombectomy outcomes of large vessel occlusion stroke secondary to underlying ICAS (ICAS-O) versus those of other ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(125 citation statements)
references
References 37 publications
4
109
0
1
Order By: Relevance
“…9 However, most studies did not report differences in 3 month clinical outcome after EVT between patients with ICAS-O and those with embolism, 7,[10][11][12][13][14][15][16]26 which has also been highlighted by a recent meta-analysis. 31 These studies reported that 16% to 89% of patients with ICAS-O required stenting, and many were treated with tirofiban. 6,7,12,26 One study found that rescue stenting, tirofiban treatment, or repeated thrombectomy resulted in favorable outcomes in 45% of pa- tients with ICAS-O who underwent instant vascular reocclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, most studies did not report differences in 3 month clinical outcome after EVT between patients with ICAS-O and those with embolism, 7,[10][11][12][13][14][15][16]26 which has also been highlighted by a recent meta-analysis. 31 These studies reported that 16% to 89% of patients with ICAS-O required stenting, and many were treated with tirofiban. 6,7,12,26 One study found that rescue stenting, tirofiban treatment, or repeated thrombectomy resulted in favorable outcomes in 45% of pa- tients with ICAS-O who underwent instant vascular reocclusion.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, they tend to be younger and have less severe initial clinical symptoms, which are associated with better developed collaterals, while CA-O is associated with more severe initial symptoms and higher rates of hemorrhagic transformation. 28,31 Moreover, adequate rescue treatment including angioplasty, stenting, and administration of glycoprotein IIb/IIIa inhibitors has been used in patients with ICAS-O and AT-O. Thus, the functional outcomes were overall similar among patients with AT-O, ICAS-O, and CA-O.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of the patients was higher in the tirofiban group than in the non-tirofiban group (non-tirofiban group versus tirofiban group; 63 [55-75] versus 71 [61-78], p = 0.015). The median initial NIHSS scores (15 [12][13][14][15][16][17][18][19][20][21] versus 14 [10][11][12][13][14][15][16][17][18][19][20], p = 0.322) and the median ASPECTS scores (8 [4.5-9.5] vs. 8 [6][7][8][9], p = 0.530) did not significantly differ between the two groups. Further, the intravenous recombinant tissue plasminogen activator (rtPA) did not significantly differ between the two groups (49.2% versus 33.9%, p = 0.093).…”
Section: Demographics and Baseline Characteristicsmentioning
confidence: 99%
“…However, if the occlusion is caused by intracranial atherosclerotic stenosis (ICAS), these MT methods may not be sufficient for recanalization and reperfusion, and rescue treatment are frequently required following MT [6][7][8][9]. Until now, angiographic and clinical outcomes after ERT for ICAS-LVO have been reported to be challenging [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the rescue strategy for failed MT in dealing with ICAS-LVO was undetermined. It had been illustrated that rescue therapies were often required for full recanalization of ICAS-LVO, which might increase the complexity of the procedure and prolong the procedure time [5,29]. However, there is a lack of study focusing on the optimal rescue strategy for ICAS-LVO, which is a pending issue in clinical practice.…”
Section: Treatment Of Icas-lvo At the Acute Stagementioning
confidence: 99%